MODERN METHODS FOR DIAGNOSING LACTASE DEFICIENCY - Xidirova Sojida Husniddin qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Lactase deficiency (LD) refers to a disruption of lactase enzyme activity or its complete absence, which in turn reduces the body’s ability to digest lactose. This thesis analyzes modern diagnostic methods for identifying lactase deficiency, including genetic tests, breath tests, and various laboratory analyses. The use of these methods provides opportunities for effective treatment and dietary planning for patients.